The influence of the ‘grammatici’ and ‘rhētores’ in the‘Corpus Hermeticum’ 18 (11-16) - Lira, David Pessoa de (Romanitas - Revista de Estudos Grecolatinos, 2026)
This article focuses on and examines the Corpus Hermeticum 18, which falls within the scope of the History of Ancient Mediterranean Religions and the History of Philosophy. Thus, the objective is to analyze the influence of grammatici and rhētores on the Hermetic treatises, more specifically on the aforementioned treatise, considering its historical-philosophical correlation with the Second Sophistic. Accordingly, it demonstrates the influence of grammatici and rhētores through the presence of Atticism, particularly the occurrences of verba composita or verba nova. Finally, it concludes that the panegyrist employed rhetorical paretymological techniques, similar to those found in Plato’s Cratylus dialogue. In particular, this article shows that the study of Hellenistic rhetoric in Corp. Herm. 18 paves the way for a deeper understanding of Late Antiquity’s literary practices, revealing that Hermetic production was not isolated from the broader intellectual and rhetorical influences of its time. Lastly, this analysis of the interaction between Hermetic teachings and rhetorical principles allows for a more comprehensive approach to the transmission and composition of Hermetic texts, highlighting their complexity and stylistic sophistication. Thus, the inclusion of treatise 18 in the Corpus Hermeticum should not be seen merely as an editorial accident but rather as a reflection of the intersection between literature, rhetoric, and philosophy in Hellenistic Egypt under Roman rule.
Keywords: Grammatici; Rhētores; Corpus Hermeticum; Paretymology; Atticism; Second Sophistic